2015
DOI: 10.1177/0009922815589912
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Exposure Among Children Younger Than Six Years in the United States

Abstract: This study investigates marijuana exposures among children <6 years old in the United States using data from the National Poison Data System. From 2000 through 2013, there were 1969 marijuana exposures among children <6 years old and an exposure rate of 5.90 per million children. The mean age of an exposed child was 1.81 years (median = 1.58 years). The majority of the children were exposed through ingestion (75.0%), and 18.5% of exposures required admission to a health care facility. The rate of marijuana exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 17 publications
3
64
0
Order By: Relevance
“…2 Second, accidental ingestion by and poisonings of young children may occur because edibles often look like candy or baked goods. 5 These products are also attractive to adolescents as it makes it easier to conceal use. 6 Finally, unintentional driving while under the influence may result (given delayed effects observed for edibles).…”
Section: Introductionmentioning
confidence: 99%
“…2 Second, accidental ingestion by and poisonings of young children may occur because edibles often look like candy or baked goods. 5 These products are also attractive to adolescents as it makes it easier to conceal use. 6 Finally, unintentional driving while under the influence may result (given delayed effects observed for edibles).…”
Section: Introductionmentioning
confidence: 99%
“…From 2000 to 2006, there was no significant change (0.6 % per year; 95 % CI −2.0 to 3.3 %) in the annual rate of marijuana exposure per 1 million <6-year-old children [40]. However, the rate increased significantly by 147.5 % (15.0 % per year; 95 % CI = 12.2 to 17.8 %) from 2006 (4.21) to 2013 (10.42) [40]. The impact recreational/retail marijuana legalization has on unintentional exposures has yet to evaluated.…”
Section: Unintentional Pediatric Exposuresmentioning
confidence: 94%
“…Concern exists that more severe effects and hospital admissions may be due to availability of higher concentration products where commercialization of marijuana has occurred. A similar study evaluating marijuana exposures in children less than 6 years of age from 2000 to 2013 found that the rate of marijuana exposure was significantly (2.82 times) higher in states where its use was legalized prior to 2000 compared with states where its use is not legal [40]. From 2000 to 2006, there was no significant change (0.6 % per year; 95 % CI −2.0 to 3.3 %) in the annual rate of marijuana exposure per 1 million <6-year-old children [40].…”
Section: Unintentional Pediatric Exposuresmentioning
confidence: 96%
See 1 more Smart Citation
“…In June 2015, findings of an academic study (Onders, Casavant, Spiller, Chounthirath, & Smith, 2015) reported on rates of paediatric (aged six and younger) marijuana exposures in the United States. In their findings, the study authors noted that the low rate (5.9 per every 1,000,000) indicates these exposures are ''rare'' and that between 2006 and 2013 the total numbers increased from roughly 100 to 250, yet headlines and articles reported these numbers in percentages: …”
Section: Colo Kids Get Into Pot Candy Prompt Calls For Childproof Pmentioning
confidence: 99%